Cost-Effectiveness and Budget Impact Analyses of Selective Internal Radiation Therapy versus Atezolizumab Plus Bevacizumab from a German Statutory Health Insurance Perspective - Schwander B; Klesper K; Rossol S; Herrmann K; Zoellner YF (Dove Medical Press, 2024)
Bjoern Schwander,1 Katharina Klesper,2 Siegbert Rossol,3 Ken Herrmann,4 York Francis Zoellner5 1Department of Health Economics & Outcomes Research, AHEAD GmbH, Bietigheim-Bissingen, Baden-Württemberg, Germany; 2Department of Health Economics & Epidemiology, ECON-EPI, Meerbusch, Nordrhein-Westfalen, Germany; 3Medical Clinic, Krankenhaus Nordwest, Frankfurt a.M., Hessen, Germany; 4Department of Nuclear Medicine, University of Duisburg-Essen, and German Cancer Consortium (DKTK)-University Hospital Essen, Essen, Nordrhein-Westfalen, Germany; 5Department of Health Sciences, University of Applied Sciences Hamburg, Hamburg, GermanyCorrespondence: Bjoern Schwander, AHEAD Gmbh, Wilhelm-Leibl-Straße 7, Bietigheim-Bissingen, D-74321, Germany, Tel + 49 1577 194 8125, Email bjoern.schwander@ahead-net.dePurpose: To compare personalized dosimetry with yttrium-90 (90Y)-loaded glass microspheres (SIRT) vs atezolizumab and bevacizumab (A+B) in hepatocellular carcinoma (HCC) treatment in terms of cost-effectiveness and budget impact from a German statutory health insurance (SHI) perspective.Patients and Methods: Cost-effectiveness analysis (CEA) and budget impact analysis (BIA) models were developed in MS Excel. The available key studies (IMbrave150 and DOSISPHERE-01) suggest that both strategies are comparable in terms of progression-free survival and overall survival in HCC, but a difference in severe adverse events (SAE) in favor of SIRT was observed. Accordingly, the CEA model investigates the endpoints "cost per SAE avoided" and "cost per quality-adjusted life year (QALY) gained", whereas the BIA simulates the impact of a stepwise re-allocation of current market share to the option which emerges as more cost-effective from the CEA.Results: The model suite estimated a mean annual total per-patient costs of € 29,984 for SIRT, compared to € 75,725 for A+B. SIRT was associated with a lower number of SAE and a higher number of QALYs compared to A+B. Switching additionally 25% of the eligible patients (≈500) from systemic therapy to SIRT could generate annual savings of approximately € 22.6 million Euros to the SHI.Conclusion: SIRT was identified as dominant treatment strategy. SIRT use not only saves SHI expenditure compared to systemic immunotherapy but also yields extra QALYs. This positions SIRT as the dominant and more cost-effective treatment strategy for patients with HCC. The savings to the SHI system, derived from the BIA conducted, become increasingly significant with rising adoption rates of SIRT.Keywords: selective internal radiation therapy, atezolizumab, bevacizumab, hepatocellular carcinoma, cost-effectiveness, budget impact